Mirabegron induces selective changes in the faecal microbiota of HFHFr rats without altering bile acid composition - Bentanachs, Roger; Miró, Lluïsa; Ramírez-Carrasco, Patricia; Sánchez, Rosa M.; Bernabeu, Manuel; Amat, Concepció; Alegret, Marta; Pérez-Bosque, Anna; Roglans, Núria; Laguna, Juan C. (Frontiers in Pharmacology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver (MASL), the initial, asymptomatic stage of the metabolic dysfunction-associated steatotic liver disease, is directly involved in the progression to steatohepatitis. Healthy lifestyle and dietary measures are currently the only treatments for MASL. Given the high prevalence of MASL in the human population, candidate drugs for its prevention or treatment should have an acceptable safety profile. Repurposing drugs already in clinical use could help to identify effective and safe drug treatments for MASL. We have characterized a high-fat, high-fructose rat dietary model of simple hepatic steatosis to evaluate the potential anti-steatotic effect of mirabegron, which is already in clinical use for the treatment of overactive bladder. We have previously reported that mirabegron administration was unable to reduce liver triglyceride content in our rat model.MethodsIn the present work, we analyse stored liver, adipose tissue (perigonadal and brown), serum and faecal samples from our previous study and present new biochemical, faecal metabolomic and microbiome data.Results and discussionWe show that oral administration of mirabegron significantly increases the expression of uncoupling protein 1 in brown adipose tissue and β3-Adrenergic receptor protein in perigonadal white adipose and liver tissues. Furthermore, mirabegron treatment changes the relative abundance of several genus and families of rat faecal microbiota, albeit without restoring the global biodiversity and evenness indexes observed in control rats, as well as faecal bile acids composition. These changes are probably due to a direct effect of mirabegron on the gut microbiome, rather than being mediated by changes in bile acid induced by drug treatment.